'Il parle normal, il parle comme nous': self-reported usage and attitudes in a banlieue. Issue 2 (31st July 2018) - SECOVA, MARIA; GARDNER-CHLOROS, PENELOPE; ATANGANA, FRÉDÉRIQUE
ABSTRACT: We report on a survey of language attitudes carried out as part of a project comparing youth language in Paris and London. 1 As in similar studies carried out in London (Cheshire et al., 2008 ), Berlin (Wiese, 2009 ) and elsewhere (Boyd et al., 2015 ), the focus was on features considered typical of 'contemporary urban vernaculars' (Rampton, 2015 ). The respondents were pupils aged 15–18 in two secondary schools in a working-class northern suburb of Paris. The survey included (1) a written questionnaire containing examples of features potentially undergoing change in contemporary French; (2) an analysis of reactions to extracts from the project data: participants were asked to comment on the speakers and the features identified. Quantitative analysis had shown that some of these features are more widespread than others and are used by certain categories of speaker more than others (Gardner-Chloros and Secova, this volume). This study provides a qualitative dimension, showing that different features have different degrees of perceptual salience and acceptability. It demonstrates that youth varieties do not involve characteristic features being used as a 'package', and that such changes interact in a complex manner with attitudinal factors. The study also provides material for reflection on the role of attitude studies within sociolinguistic surveys.